Hyperosmolar nonketotic coma precipitated by lithium-induced nephrogenic diabetes insipidus. Issue 867 (January 1998) - Azam, H.; Newton, R. W.; Morris, A. D.; Thompson, C. J.
Abstract : A 45-year-old man, with a 10-year history of manic depression treated with lithium, was admitted with hyperosmolar, nonketotic coma. He gave a five-year history of polyuria and polydipsia, during which time urinalysis had been negative for glucose. After recovery from hyperglycaemia, he remained polyuric despite normal blood glucose concentrations; water deprivation testing indicated nephrogenic diabetes insipidus, likely to be lithium-induced. We hypothesize that when this man developed type 2 diabetes, chronic polyuria due to nephrogenic diabetes insipidus was sufficient to precipitate hyperosmolar dehydration.